The Purification and Concentration of Hog Cholera Virus with Electron Micrographs: (A Preliminary Note) - Cunliffe, H. R. (1968)
Cell-cultured hog cholera virus was partially purified by chromatography on pulverized magnetic ferric oxide. Infectivity yields of 50 to 100% were obtained with a 90 to 95% reduction in extraneous organic nitrogen. Concentration and further purification of infectious virus were achieved by rate-zonal and isopycnic ultra-centrifugations in buffered cesium chloride. Density determinations obtained from the isopycnic experiments indicate a buoyant density of 1.14-1.15 gm/ml for the strain of virus used. Electron microscopy of negatively stained samples of concentrated infective virus from one isopycnic experiment revealed 40- to 40-mµ virus-like particles and a large number of 12- to 15 mµ entities. The 40- to 50-mµ particles were surrounded by a poorly defined, asymmetrically arranged sac-like membrane or appendage. It is suggested that the images of the 40- to 50-mµ particles represent the infective virion of hog cholera virus.